Gravity induced spontaneous radiation - Ding-fang Zeng (Nuclear Physics B, 2023)
We suggest that behind the black hole information paradox is a new and universal radiation mechanism, Gravity Induced Spontaneous Radiation, or GISR hereafter. This mechanism happens to all kinds of compositional objects and it requires only their microscopic structure as the basis. It's always accompanied with such inner structures' variation and allows for explicitly hermitian hamiltonian description. For black holes, by Wigner-Wiesskopf approximation we show that such a radiation has a thermal spectrum exactly the same as hawking radiation; while through numeric integration, we show that the variation of the radiation particles' entropy exhibits all features of Page curve as expected. We also provide exact and analytic solutions to the Einstein equation describing microscopic structures required by the GISR of black holes and show that, after quantisation the degeneracy of wave functions corresponding with those solutions are consistent with the area law formula of Bekenstein-Hawking entropy.